(untitled) (GANIT: Journal of Bangladesh Mathematical Society, 2011)
In this paper, we use the integration technique together with the finite element method to approximate the numerical solution of an initial value problem of differential equations. The function of two variables is expanded into Taylor’s series up to order two. We exploit Gauss- Legendre quadrature rules evaluating the integrals arising in the formulation of the present method to get the better accuracy. GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 30 (2010) 51-58 DOI: http://dx.doi.org/10.3329/ganit.v30i0.8503